Disclosure of HIV Status to Children in Sub-Saharan Africa: A Systematic Review - Abdul-Razak Doat; Reza Negarandeh; Marzieh Hasanpour (Medicina, 2019)
Background and objectives: This study aimed to assess the level of HIV disclosure to children in sub-Saharan Africa as it relates to prevalence of disclosure, barriers, merits and demerits, timing of disclosure, and factors that promote parents and caregivers’ decisions to disclose the information. Materials and Methods: A systematic literature search was performed using the following online databases: PubMed, Google Scholar, Web of Science, Scopus, and Embase, to obtain relevant articles on HIV disclosure to children in sub-Saharan Africa. The following search terms were used: “HIV” AND “Disclosure” AND “Sub-Saharan Africa” AND “Children”. Results: A total of 18 articles were included in this systematic review. The studies on HIV status disclosure to children in sub-Saharan Africa included a total of 1343 HIV-positive children and 1879 caregiver/child or healthcare worker-child dyads, from the following countries: Ethiopia, South Africa, Ghana, Kenya, Cote d’Ivoire, Burundi, Cameroon, Democratic Republic of Congo, Uganda, Burkina Faso, and Zambia. The prevalence of HIV disclosure ranged from as low as 9% to 72%. Age was a major factor associated with disclosure. Conclusions: HIV status disclosure to children is quite low in sub-Saharan Africa. This is a result of multiple factors such as parents’/caregivers’ fear of the child disclosing status to others, a lack of knowledge on how the disclosure should be made, and the assertion that the children are young and cannot withstand the psychological impact of diagnosis.